Enhancement of Coal Permeability Using Aqueous NaCl with Microwave Irradiation - Weiming Guan; Qi Qi; Senlin Nan; Haichao Wang; Xin Li; Yingyuan Wen; Junhui Yao; Yanyan Ge (Geofluids)
Water in coal pores can generate strong steam explosions when treated with microwave irradiation. In order to improve the sensitivity of coal reservoirs to microwaves, we used varying concentrations of NaCl on the pore solution, which further increased the effect of microwaves on permeability enhancement. In our experiments, we selected 3 ratios of water content and 5 different concentrations of NaCl. The changes of coal water content and permeability before and after irradiation were compared. In addition, changes in coal surface temperature and internal thermal power were analyzed through thermal imaging and random sphere numerical modeling. Results showed that the increase of the proportion of solution mass and the ion concentration in the solution improved the overall dielectric properties of coal rock samples. After microwave irradiation, the average reduction rate of water content in coal rock samples increased with the increase of ion concentration in the solution. Both the average surface temperature of the coal rock samples and the average electromagnetic heating power gradually increased; this increases the temperature rise rate and maximum temperature of coal rock samples under the same irradiation time, which is conducive to better rapid accumulation of steam pressure, thereby improving the pore structure more effectively. Finally, the maximum growth rate of permeability reached 466.18%. This work provides a novel train of thought to enhance coal permeability by using microwave irradiation.